New hybrid scaffolds based on ASA/genistein: Synthesis, cytotoxic effect, molecular docking, drug-likeness, and in silico ADME/Tox modeling - Lizeth Gómez-R, Gustavo Moreno-Q, Angie Herrera-R, Wilson Castrillón-L, Andrés F. Yepes, Wilson Cardona-G (Journal of Applied Pharmaceutical Science, 2022)
Eight hybrids based on genistein and aspirin were designed, synthesized, and elucidated by spectroscopic analysis. Chemopreventive potential of these compounds was evaluated against SW480 human colon adenocarcinoma cells, its metastatic derivative SW620 and normal cells (CHO-K1). According to the results, hybrids 4a and 4c displayed significant activity over SW480 cells causing a reduction of cell viability of 40.49% and 40.39%, respectively, when treated with 300 µM for 48 hours, being time- and concentration-dependent. None of the compounds exhibited activity at 24 hours; besides, these types of molecules were not active on human metastatic SW620 cells (data not shown). On the other hand, compounds 4d, 4e, 4f, and 4h did not display any activity on the cells at the conditions evaluated. Multitarget docking studies performed against six tumor-associated proteins targets in colorectal cancer, would reveal that hybrids 4a and 4c may inhibit function of Polo-like kinase 1 as primary mode of action with a binding affinity about −10 kcal/ mol. However, docking action would suggest these compounds may induce synergistic cytotoxic effects by regulation of B-cell lymphoma 2 (Bcl-2)/Bcl-2-associated X protein system and cyclooxygenase-2 in SW480 colorectal cancer cells with Vina scores in the range −10.1 to −9.3 kcal/mol. Additionally, in silico drug-likeness studies suggest that active hybrids 4a and 4c display favorable pharmacokinetics indices, good Absorption, Distribution, Metabolism and Excretion (ADME)/Tox profile, and a remarkable metabolic stability within recommended therapeutic ranges, making these compounds useful as promising medicinal scaffolds in the designing of novel orally active anticancer candidates.
Keywords: Genistein, acetylsalicylic acid (ASA), hybrids, cytotoxicity, colorectal cancer, in silico ADME/Tox profile, molecular docking